Learning and Fullfilment of Children’s Right in the New Normal Era at Islamic Elementary School (Proceeding of Saizu International Conference on Transdisciplinary Religious Studies, 2021)
Learning in the new normal requires various adjustments to existing conditions in order to remain able to achieve the goals. These adjustments are needed so that children's rights are still fulfilled during the learning process, especially at the basic education level, where the potential of students is in a period of great development. In this regard, this research was conducted with the aim of comprehensively describing how learning is carried out in one of the Islamic elementary schools in Banyumas, namely MI Miftahul Huda. while still fulfilling the rights of the children in it. The methods used in collecting data include observation, interviews and documentation. The results showed that the adjustments made in the learning process specifically includes learning methods and media, flexibility of place and time to study, and how to access learning resources. With this adjustment, students at these institutions have the opportunity to receive learning materials, find and access learning resources and do assignments and present the skills they have acquired according to their level of intelligence and age